The role of dopamine and endocannabinoid systems in prefrontal cortex development: Adolescence as a critical period - Peters, Kate Zara; Naneix, Fabien (Frontiers in Neural Circuits, 2022)
The prefrontal cortex plays a central role in the control of complex cognitive processes including action control and decision making. It also shows a specific pattern of delayed maturation related to unique behavioral changes during adolescence and allows the development of adult cognitive processes. The adolescent brain is extremely plastic and critically vulnerable to external insults. Related to this vulnerability, adolescence is also associated with the emergence of numerous neuropsychiatric disorders involving alterations of prefrontal functions. Within prefrontal microcircuits, the dopamine and the endocannabinoid systems have widespread effects on adolescent-specific ontogenetic processes. In this review, we highlight recent advances in our understanding of the maturation of the dopamine system and the endocannabinoid system in the prefrontal cortex during adolescence. We discuss how they interact with GABA and glutamate neurons to modulate prefrontal circuits and how they can be altered by different environmental events leading to long-term neurobiological and behavioral changes at adulthood. Finally, we aim to identify several future research directions to help highlight gaps in our current knowledge on the maturation of these microcircuits.